The Effect of Different Organic Fertilizers on Soil Properties in Tolering Climate Change - DIZIKISA, Tülay; YILDIZ, Nesrin (MAS Journal of Applied Sciences, 2023)
Climate change is an important global problem. Sustainable agriculture is an important choice to mitigate climate change. Soil has gradually lost its organic matter over the past centuries. One of the practices encouraged to combat climate change is to increase soil organic matter. The best way to increase organic matter is the widespread use of organic fertiliser. The use of organic fertilisers can improve crop yield and soil properties while preventing pests and diseases. Soil carbon sequestration is a process in which CO2 is removed from the atmosphere and stored in the soil carbon pool. The aim of this review is to discuss how the use of fertilisers of organic origin with different properties can reduce the adverse effects of atmospheric carbon increase on global warming, whether from agricultural activities or from urban, industrial or transport activities.